Ship sanitation: controlling and Preventing of Risk Factors for Disease Transmission in The Port of Kendari - Yetty Septiani Mustar (Journal of Health Science and Prevention, 2021)
The spread of infectious diseases globally has been a threat to public health and national economies for many centuries. One of the undeniable sectors that contributed to the spread of disease is maritime transport. This research aimed to examine ship sanitation for controlling and preventing the potential risk of disease transmission. This study used an observational survey method, with a sample of 24 ships that anchored in the port of Kendari by using an accidental sampling technique. Findings from this research revealed that there were ships with high-risk sanitation categories or have unqualified levels of sanitation. The main determinants that contribute to accelerating the global transmission of many infectious diseases on the ship are the sign and presence of vectors. Outbreaks associated with the presence of vectors on board are usually related to inadequate control and sanitation along with insufficient attention to preventing contamination. Therefore, the crewmember on board needs to increase their knowledge through various ship sanitation training, develop sanitation programs and integrate sustainable monitoring and evaluation programs of vectors toimprove sanitation as an effort to prevent risk factors for disease transmission.